Systematic evaluation during early-phase ischemia predicts outcomes in middle cerebral artery occlusion mice. Issue 1 (6th January 2021) - Xiao, Xiang-Tian; Luo, Chun; Yuan, Yuan; Xiao, Li; Qu, Wen-Sheng
Abstract : Identifying outcome predictors for ischemic stroke is beneficial for choosing correct intervention protocols. Thus, it is necessary to systemically evaluate histological outcome-associated changes such as hemodynamics, behavior, and body weight during the early phase of ischemia. Here, 50 mice were subjected to 45-min middle cerebral artery occlusion (MCAO) using Longa's method. Hemodynamic changes were monitored by Doppler laser probe, and behaviors were evaluated by scales while the tissues were visualized by staining. The results by correlation analysis demonstrated that with a probe located near the posterior boundary zone of MCA territory, the latency of anoxic depolarization, as well as the cerebral blood flow reduction during MCAO were confirmed to be predictors for the infarct volume on day 3 post-ischemia; histology showed that the risk of a space-occupying secondary hemorrhage was significantly correlated with the increase of infarct volume versus the traditional Bederson's neurological deficit scale, a renewed combined behavioral scoring method performed nicely to reflect the severity of tissue lesions. Weight loss was a valuable metric for the enlargement of both infarct volume and secondary hemorrhage. Monitoring changes during early-phase ischemia may benefit the optimization of ischemia models and the discovery of potential intervention targets. See Video Abstract, http:/links.lww.com/WNR/A601 ). Abstract : Supplemental Digital Content is available in the text.